The Effects of Illicit Drugs on the HIV Infected Brain (2008)
ABSTRACT: Evidence accumulating from clinical observations, neuroimaging and neuropathological studies suggests that illicit drug abuse accentuates the adverse effects of HIV on the central nervous system (CNS). Experimental investigation in cell culture models supports this conclusion. Injecting drug abuse is also a risk factor for the acquisition of HIV infection, the incidence of which continues to rise in intravenous drug users (IVDU) even in countries with access to effective therapy. In order to understand the interactions of drug abuse and HIV infection, it is necessary to examine the effects of each insult in isolation before looking for their combined effects. This review traces progress in understanding the pathogenesis of HIV related CNS disorders before the introduction of effective therapy and compares the state of our knowledge now that effective therapy has significantly modified disease progression. The additional impact of intravenous drug abuse on HIV-associated brain disease, then and now, is also reviewed. Predictions for the future are discussed, based on what is known at present and on recently emerging data.